2019
DOI: 10.1124/mol.118.114439
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated Transcriptional Regulation of Cytochrome P450 3As by Nuclear Transcription Factor Y and Specificity Protein 1

Abstract: The cytochrome P450 3A subfamily plays vital roles in the metabolism of endogenous chemicals and xenobiotics. Understanding the basal expression of CYP3A in humans and pigs is crucial for drug evaluation. In this study, we demonstrated that the basal transcriptional regulation of CYP3A genes in hepatocytes is evolutionarily conserved between humans and pigs. The basal expression of CYP3A genes is transactivated by two cisacting elements, the CCAAT and GC boxes, located a constant distance apart in the proximal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Transcriptional regulation of CYP3A5 has not been widely investigated. Only a few nuclear receptors, such as NF-Y [47], SP1 [47], CAR [48], AR [49], HNF-4α, and PXR/ RXRα [50] have been identi ed as possible factors involved in the transcriptional expression of CYP3A5, mainly in liver and prostate cancer. Nuclear receptors regulate transcription by binding to DNA response elements (AGGTCA half-sites).…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptional regulation of CYP3A5 has not been widely investigated. Only a few nuclear receptors, such as NF-Y [47], SP1 [47], CAR [48], AR [49], HNF-4α, and PXR/ RXRα [50] have been identi ed as possible factors involved in the transcriptional expression of CYP3A5, mainly in liver and prostate cancer. Nuclear receptors regulate transcription by binding to DNA response elements (AGGTCA half-sites).…”
Section: Discussionmentioning
confidence: 99%
“…Previous works have demonstrated that CYP3A constitutive expression is regulated by nuclear transcription factor Y; specificity protein 1 [81,82]; hepatocyte nuclear factors 1α, 3γ and 4 [83][84][85]; upstream stimulatory factor 1 [86]; activator protein 1 [87] and CCAAT/enhancer-binding proteins α and β [85,86]. In the presence of xenobiotics, induced expression of CYP3A is mediated by Pregnane X Receptor [80], constitutive androstane receptor (CAR), glucocorticoid receptor (GR) and vitamin D receptor (VDR) [81,88,89].…”
Section: Discussionmentioning
confidence: 99%